Distinguished Figures in Mechanism and Machine Science: Their Contributions and Legacies - Ceccarelli, Marco; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2007)
This is the ?rst volume of a series of edited books whose aim is to collect contributed papers in a framework that can serve as a dictionary of names of individuals who have made contributions to the discipline of MMS (Me- anism and Machine Science). This dictionary project has the peculiarity that, through descriptions of the ideas and work of these individuals, the papers will illustrate mainly technical developments in the historical evolution of the individual ?elds that today de?ne the scope of MMS. Thus the core of each contribution will be a survey of biographical notes describing the efforts and experiences of these people. Finding appropriate technical experts as authors for such papers and - couraging them to write them has been a challenge; it is a demanding and time-consuming effort to produce such in-depth articles that delve deeply into the historical background of their topics of expertise. This ?rst volume of the dictionary project has been possible thanks to the invited authors who have enthusiastically shared the initiative and have spent time and effort in prep- ing papers that have the novel characteristics of survey and historical notes. The papers in this volume cover the wide ?eld of the History of Mechanical Engineering with speci?c focus on MMS. I believe that a reader who takes advantage of the papers in this book, as well as future ones, will ?nd further satisfaction and motivation for her or his work (historical or not).
Archimedes (287–212 BC) -- Agustín de Betancourt y Molina (1758–1824) -- Oene Bottema (1901–1992) -- William Kingdon Clifford (1845–1879) -- Nicolaus Copernicus (1473–1543) -- Alexander Yershov (1818–1867) -- Ferdinand Freudenstein (1926–2006) -- Kurt Hain (1908–1995) -- Heron of Alexandria (c. 10–85 AD) -- Willibald Lichtenheldt (1901–1980) -- Xian-Zhou Liu (1890–1975) -- Giulio Mozzi (1730–1813) -- Théodore Olivier (1793–1853) -- Ufimtsev anatoly georgievich (1880–1936) -- James Watt (1736–1819) -- Walter Wunderlich (1910–1998).
Keywords: Engineering design; Machinery; History; Engineering Design; Machinery and Machine Elements; History of Science